Bacillus circulans GN03 Alters the Microbiota, Promotes Cotton Seedling Growth and Disease Resistance, and Increases the Expression of Phytohormone Synthesis and Disease Resistance-Related Genes - Qin, Lijun; Tian, Peidong; Cui, Qunyao; Hu, Shuping; Jian, Wei; Xie, Chengjian; Yang, Xingyong; Shen, Hong (Frontiers in Plant Science, 2021)
Plant growth-promoting bacteria (PGPB) are components of the plant rhizosphere that promote plant growth and/or inhibit pathogen activity. To explore the cotton seedlings response to Bacillus circulans GN03 with high efficiency of plant growth promotion and disease resistance, a pot experiment was carried out, in which inoculations levels of GN03 were set at 104 and 108 cfu·mL-1. The results showed that GN03 inoculation remarkably enhanced growth promotion as well as disease resistance of cotton seedlings. GN03 inoculation altered the microbiota in and around the plant roots, led to a significant accumulation of growth-related hormones (indole acetic acid, gibberellic acid, and brassinosteroid) and disease resistance-related hormones (salicylic acid and jasmonic acid) in cotton seedlings, as determined with ELISA, up-regulated the expression of phytohormone synthesis-related genes (EDS1, AOC1, BES1, and GA20ox), auxin transporter gene (Aux1), and disease-resistance genes (NPR1 and PR1). Comparative genomic analyses was performed between GN03 and four similar species, with regards to phenotype, biochemical characteristics, and gene function. This study provides valuable information for applying the PGPB alternative, GN03, as a plant growth and disease-resistance promoting fertilizer.